Perspectives and progress of ecology and conservation science in the Azores: the possible contribution of Artificial Intelligence - Borges, Paulo A. V. (2014)
EPIA 2013 - XVI Portuguese Conference on Artificial Intelligence Angra do Heroísmo, Azores, Portugal, 9 – 12 September.